The macroeconomic conditions of EU-inspired employment policies - János Gács (Hungarian Academy of Sciences, Institute of Economics, 2006)
With its impulses and coordination initiatives the EU makes efforts to influence the employment and labour policies in its Member States. Here the principal instruments are the European Employment Strategy and its main constituent, the Employment Guidelines. The latter, while based on modern professional ideas about the institutional determinants of the labour market, have been incomplete up to 2005: due to departmentalism reflected in the tensions between the EU institutions responsible for employment and macro-policies crucial fields were kept out of the employment guidelines such as wage-setting policies, the wage bargaining system as well as the budgetary implications of active labour market policies. The macroeconomic support of the EU-inspired employment policies is theoretically not sound. An example of this is the objective of the Lisbon Process of simultaneous ambitions improvement of both macro-level productivity and employment. This target ignores the trade-off between these two factors prevailing even in the long term. The division and inconsistency between the philosophy and operation of various EU institutions is reflected in the moderate, but disturbing inconsistencies between the mid-term macroeconomic and employment strategies of the Hungarian government (the Convergence Programme and the National Action Plan for Employment). There are, however, possibilities for the member countries, including Hungary, to prepare and carry out employment policies in the EU framework that are supported by sound macro-policies: they have to be less slavish abiding by specific EU recommendations, have to take into account the domestic conditions realistically, and get rid of detrimental institutional divisions, at least in their indigenous administration.
Keywords: F15; E61; J20; O11; 330; European integration; employment strategy; coordination of policies